Pelatihan Sistem Sertifikasi International Sustainability and Carbon Certification (ISCC) di Industri Oleokimia Pengolahan Bahan Baku Berbasis Kelapa Sawit - Tambunan, Pravil Mistryanto; Juniar, Anna; Rajali, Mariany; Saputri, Muharni; Kembaren, Fanny (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
This community service activity aims to provide training on the International Sustainability and Carbon Certification (ISCC) system to employees of a palm oil-based oleochemical industry company that processes residues and waste from palm oil derivative products. The training utilized a blended learning approach with pre-test and post-test evaluation using 20 multiple-choice questions, involving 30 participants. The results showed a significant improvement in participants' understanding, with average pre-test scores of 62.3 (SD=15.8) increasing to 87.7 (SD=9.4) on post-test, indicating an improvement of 25.4 points (40.7%, p<0.001). Twenty-one participants (70%) achieved excellent category (90-100) on post-test compared to only 6 participants (20%) on pre-test. Participant satisfaction reached 4.6/5.0 with 83.3% expressing high satisfaction. Follow-up after 1 month showed that 80% of participants had applied their knowledge in the workplace and 66.7% of companies began ISCC certification preparation. This activity successfully increased the human resource capacity of the oleochemical industry in understanding and implementing ISCC standards, supporting the competitiveness of Indonesian products in the global market that prioritizes sustainability aspects.